2022
DOI: 10.3390/w15010050
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Rainfall and Flood Risk Prediction over the East Coast of South Africa

Abstract: Extreme rainfall associated with mid-tropospheric cut-off low (COL) pressure systems affected the entire east coast of South Africa during April 2022, leading to flooding and destruction of homes, electricity power lines, and road infrastructure, and leaving 448 people confirmed dead. Therefore, this study investigated the evolution of the two COLs and their impacts, including the occurrence of extreme rainfall and cold weather over the southeast coast of the country. We analysed observed and reanalysis meteor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The moist wind blows from west to east of the Java Sea's wide waters and creates persistent rain events in South Sulawesi. However, the mountains in the middle of South Sulawesi act as a barrier to the monsoon wind, indicating that the influence of the northwest monsoon in the east of South Sulawesi is not as significant as that seen in the west (Mashao et al, 2023;Merz et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…The moist wind blows from west to east of the Java Sea's wide waters and creates persistent rain events in South Sulawesi. However, the mountains in the middle of South Sulawesi act as a barrier to the monsoon wind, indicating that the influence of the northwest monsoon in the east of South Sulawesi is not as significant as that seen in the west (Mashao et al, 2023;Merz et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Further research is required to determine whether changes in atmospheric circulation observed during the 2021–2022 summer in the Australian region as well as the Antarctic 29 and South Africa 30 were a response to increases in latitudinal troposphere temperature gradients as a consequence of global warming or a rare disturbance of the Southern Hemisphere atmospheric longwave pattern. For example, an increase in the meridional temperature gradient and associated baroclinic instability has been proposed for unusual planetary-scale atmospheric motions in the Northern Hemisphere 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, any deluge of rainfall from these systems was exacerbated by human factors that led to flash flooding, mudslides, infrastructure collapse, etc. For example, rural-urban migration has led to illegal infrastructure developments, more sewer demands or the blocking of drainage systems and riverbank farming, especially in wetlands or on unstable platforms [63].…”
Section: Impacts Of Colsmentioning
confidence: 99%